On the nature of flow patterns and pressure drop fluctuations during flow boiling - Oliveira, Jeferson Diehl de (2021)
This experimental and phenomenological study investigated fluctuations and characteristic frequencies of pressure drop and flow pattern during flow boiling of isobutane in a horizontal mini-channel 1.0 mm in diameter. The fluid was investigated at a saturation condition of 27◦C, heat flux ranging between 1 and 80 kW/m2 and mass flux ranging from 380 to 890 kg/(m2s). Six different flow patterns were identified based on the analysis of images captured from a high-speed camera: dispersed bubbles, plug, slug, churn, and annular (wavy and smooth). Characteristic frequencies were investigated from the time series using wavelet transform and the chaotic dynamics were studied using the largest Lyapunov exponent and phase portrait reconstruction. Results showed that pressure drop fluctuations presented predominance in low frequencies over time. On the other hand, higher frequencies in flow patterns were caused by their different morphology. Non-linear analysis showed that the nature of both pressure drop and flow pattern time series were chaotic for all flow conditions studied.